(untitled) (Colombia Medica, 2010)
Many different immunological processes have been described in the Chagas infection, some of them associated with the Chagas disease. In this scenario, the L-Arginine-Nitric oxide (NO) – Peroxynitrite (NOOO-) pathway (LANOP pathway) appears as an essential component of that process. The relationship is well known between cytokines that can induce Oxide Nitric Synthase (iNOS) genes, such as TNF-a and IFN-g, and other molecules that can inhibit their expression (TGF-b, IL-10 and others), which are involved in both acute and chronic stages of the disease pathogenesis. However the participation of the LANOP pathway seems complex, given that evidence shows different roles for it during the course of the infection. In this article, the authors review the immunological and inflammatory response leading to the activation of the LANOP pathway during the Chagas infection, and the role this via plays, including different effects, protector or deleterious, observed in parallel during the development of the infection.